Cambios tecnológico-productivos del trabajo: problemática jurídica ecuatoriana (Tema Central) - Rodríguez Mendoza, Carolina Jacqueline (2022)
The research objective has been to outline the relationships between technological and productive transformations in the work. To reach that, a qualitative methodology of documentary review and intuitive contribution was followed on the theoretical descriptive basis of concepts such as: technology, innovation, creation, social changes, productive transformations; and, mainly, employment within the framework of the concept of work. As it is a descriptive and exploratory level investigation; The relationships that have been found from the scientific literature in this area of knowledge are delineated and the possible existence of more relationships is formulated. Finally, this study exposes the importance of technological change; look at the process of technological transformation in the social context, raises the emergency or need for a new paradigm; fixes the relationship between technology, technological innovation, social change and work to conclude on its dimensions, the type of relationship and its effects; It also highlights the difficulties, limits and challenges that this issue represents for the contemporary world, especially on employment from a legal perspective illustrated in problems of the current Ecuadorian context.